Tweaking Progranulin Expression: Therapeutic Avenues and Opportunities - Terryn, Joke; Verfaillie, Catherine M.; Van Damme, Philip (Frontiers in Molecular Neuroscience, 2021)
Frontotemporal dementia (FTD) is a neurodegenerative disease, leading to behavioral changes and language difficulties. Heterozygous loss-of-function mutations in progranulin (GRN) induce haploinsufficiency of the protein and are associated with up to one third of all genetic FTD cases worldwide. While loss of GRN is primarily associated with neurodegeneration, the biological functions of the secreted growth factor-like protein are more diverse, ranging from wound healing, inflammation, vasculogenesis and metabolic regulation to tumor cell growth and metastasis. To date no disease modifying treatments exist for FTD, but different therapeutic approaches to boost GRN levels in the central nervous system are currently being developed (including AAV-mediated GRN gene delivery as well as anti-SORT1 antibody therapy). In this review, we provide an overview of the multifaceted regulation of GRN levels and the corresponding therapeutic avenues. We discuss opportunities, advantages and potential drawbacks of the diverse approaches. Additionally, we highlight the therapeutic potential of elevating GRN levels beyond patients with loss-of-function mutations in GRN.